Non-medical practitioner roles in the UK: who, where, and what factors influence their development?. (25th July 2019) - Abraham, Jenny; Bailey, Liz; Coad, Jane; Whiteman, Becky; Kneafsey, Rosie
Abstract : Background: traditional health workforce roles are changing, with existing roles being extended and advanced, while new roles are being created, often undertaking duties previously completed by doctors, sometimes referred to as non-medical practitioners (NMPs). Aim: to investigate which NMP roles exist within the UK, mapping distribution, and explore factors influencing their development and recruitment. Methods: two descriptive, exploratory, online self-completed semi-structured questionnaires were used. One was sent to all NHS acute healthcare providers (n=156) and private/independent healthcare providers in England (n=90). A separate questionnaire collected data, using convenience and snowballing approaches, from NMPs across the UK. Quantitative data were analysed using descriptive and frequency statistics. Qualitative data derived from open questions and comments were analysed using content and thematic analysis. Results: healthcare organisations in England returned 23/246 useable questionnaires; 115 NMPs returned responses, 19 did not meet the criteria, leaving 96 useable responses. Conclusion: seven NMP roles were identified, throughout the UK, with regional variation. Several factors influence the development and recruitment of NMP roles in England such as service delivery and national policies. Inconsistencies were noted in Agenda for Change pay banding. Many practitioners undertook NMP roles to progress their career clinically.